IMPLEMENTASI MODUL SEJARAH LOKAL BERBASIS MUATAN KEARIFAN LOKAL MASYARAKAT KALIMANTAN BARAT DALAM PEMBELAJARAN SEJARAH DI SEKOLAH MENENGAH ATAS - Astrini Eka Putri; Andang Firmansyah; Edwin Mirzachaerulsyah (Yupa: Historical Studies Journal, 2022)
This research is one of the phases in development research, namely the implementation phase. The purpose of this study was to describe the implementation of the local history module based on local wisdom capacities of West Kalimantan people in high school. This local history module has been validated by experts and has been tested. The research method used in this research is descriptive qualitative. The results of the study describe this module which is presented in digital form which is shared by history teachers through the school's e-learning application. This local history module has been prepared in accordance with the KD mapping in the curriculum of 2013. This local history module consists of three chapters that discuss local history based on the content of local wisdom of West Kalimantan people. Based on the results of observations, it is shown that this local history module is easy to understand and interesting to read. The existence of a local history module based on the content of local wisdom of West Kalimantan people can help students understand local traditions as a form of preserving their culture. This module is also able to influence students' interest and motivation in learning history in general.